Intro to stats board game: a board game to understand statistics - Zainuddin, Puteri Faida Alya; Banchit, Azilawati (Universiti Teknologi MARA, Kedah, 2023)
This paper discusses the development, testing, and feedback analysis for an innovative board game that enables the players to understand basic Statistics which are regarding the understanding of measurement scale, type of variable, sample, population, sampling frame, sampling techniques, and data collection method with a given problem statement. Findings have shown that students interact and understand using the game better than the normal board and chalk method. The game is ideal for those learning statistics for the first time and gauging their comprehension. This board game differs from others in that the difficulty level varies depending on the colour of the question card. Preliminarytests were also conducted among some of the players to assess the usability level and their interest in using the board game. Results have shown 75 percent of the respondents supported better understanding while having fun with the use of the board game as part of the teaching and learning process.